(untitled) (Revista Contexto & Saúde, 2026)
This study aimed at investigating the occupational therapy practices in relation to the oncological pain of hospitalized patients in palliative care. It is a descriptive study which used a qualitative approach, and counted with the participation of 10 occupational therapists acting in hospitals, specifically in infirmaries who treated oncological patients in palliative care, with minimum experience of 3 months. Procedurally, the snowball method was used and the data collection was performed via Google Meet interviews. The content was transcribed and systematized through thematic analysis. Averagely, the age of participants was 31,3 years-old, acting for 5,1 years and working with palliative care for 4,4 years. From the content gathered in the interviews, three thematic categories emerged and culminated in the systematization of seven subcategories. In this article, the focus is on the Modus operandi of the occupational therapists treating oncological pain category, which is divided into four subcategories (Work schedule, Knowledge and use of tools in pain assessment, Resources and techniques used for pain management, Documentation in medical records). Frailties were identified in the modus operandi, especially regarding the assessment process. Nonetheless, the acting characteristics presented by the occupational therapists showed associations of pain with the occupations, a relevant aspect in favor of defending the specificities of this profession.